Hormonal profiles in dormant turions of 22 aquatic plant species: do they reflect functional or taxonomic traits? - Adamec, Lubomír; Plačková, Lenka; Bitomský, Martin; Doležal, Karel (Annals of botany, 2024)
BACKGROUND AND AIMS: Turions are vegetative, dormant overwintering organs formed in aquatic plants in response to unfavourable ecological conditions. Contents of cytokinin (CK), auxin metabolites and abscisic acid (ABA) as main growth and development regulators were compared in innately dormant autumnal turions of 22 aquatic plant species of different functional ecological or taxonomic groups with those in non-dormant winter apices in three aquatic species and with those in spring turions of four species after their overwintering. METHODS: The hormones were analysed in miniature turion samples using ultraperformance liquid chromatography coupled with triple quadrupole mass spectrometry. KEY RESULTS: In innately dormant turions, the total contents of each of the four main CK types, biologically active forms and total CKs differed by two to three orders of magnitude across 22 species; the proportion of active CK forms was 0.18-67 %. Similarly, the content of four auxin forms was extremely variable and the IAA proportion as the active form was 0.014-99 %. The ABA content varied from almost zero to 54 µmol kg-1 dry weight and after overwintering it usually significantly decreased. Of all functional traits studied, hormone profiles depended most on the place of turion sprouting (surface vs bottom) and we suggest that this trait is crucial for turion ecophysiology. CONCLUSIONS: The key role of ABA in regulating turion dormancy was confirmed. However, the highly variable pattern of the ABA content in innately dormant and in overwintered turions indicates that the hormonal mechanism regulating the innate dormancy and its breaking in turions is not uniform within aquatic plants.
Keywords: kyseliny indoloctové; vegetační klid; Plant Growth Regulators; Cytokinins; functional traits; ABA; Indoleacetic Acids; Abscisic Acid; auxins; kyselina abscisová; regulátory růstu rostlin; innate and imposed dormancy; mature winter buds; phylogenetic correction; overwintering; Plant Dormancy; cytokininy; quiescence